International Liquidity Rents - Eden, Maya (World Bank, Washington, DC, 2013)
This paper presents a model of global liquidity shortages. Liquid claims are enforceable promises that play a transaction role. Since developed economies have a comparative advantage in creating liquidity, they export liquid claims to emerging economies, resulting in a permanent current account deficit. This model suggests that unrestricted liquidity flows are (a) welfare reducing for emerging economies and (b) Pareto inefficient. The inefficiency results both from excessive investment for the purpose of creating collateral-backed liquid claims, and from excessive global fragility with respect to collateral shocks.